How do human perceptions pose threats and shape conservation options for Temminck’s pangolin (Smutsia temminckii)? - Kelly Sabashau; Beaven Utete (Sustainable Environment)
Temminck’s pangolin, Smutsia temminckii (Smuts, 1832) is a threatened but protected species in Zimbabwe whose population is declining, ostensibly, due to poaching and persecution by humans. Inasmuch as the human factor is a critical dimension in Temminck’s pangolin population dynamics, there are few studies documenting local perceptions on conservation threats and options for the species in Zimbabwe. The study aimed to (a) assess the conservation perceptions of local fringe communities and (b) explore existing and potential conservation options for Temminck’s pangolin in Hwange National Park (HNP) in Zimbabwe. Data on local perceptions towards Temminck’s pangolin were collected through a questionnaire survey from May to December 2021, delving across cultural, political, economic, and social aspects in HNP. Poaching and trafficking, spurred by lucrative market prices and frivolous superstitious cultural beliefs and myths associated with the species and its by-products, are the apex drivers for Temminck’s pangolin dynamics in HNP. Climate change and habitat degradation mostly by African savanna elephants also affect Temminck’s pangolin populations in the HNP. A multifaceted conservation approach integrating indigenous knowledge systems, citizen science data, active community involvement, modern conservation methods, and a zero pangolin poaching policy in HNP is imperative for Temminck’s pangolin conservation.